2015
DOI: 10.1007/s00253-015-6746-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characteristics of a Ca2+-dependent endoglucanase from Cytophaga hutchinsonii

Abstract: Cytophaga hutchinsonii is a Gram-negative bacterium that can degrade crystalline cellulose efficiently with an unknown strategy. Genomic analysis suggested it lacks exoglucanases which are found in many cellulolytic organisms and most of the cellulases in C. hutchinsonii lack recognizable carbohydrate-binding modules (CBMs). CHU_1280, speculated to be an endoglucanase belonging to glycoside hydrolase family 9 (GH9) in C. hutchinsonii, was functionally expressed in Escherichia coli, and evidence was presented s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
9
1
2
Order By: Relevance
“…The crystal structure of Cel5B supports this suggestion, since the predicted open active site is consistent with a nonprocessive mode of action. Our results indicating the lack of processivity of Cel5B and Cel9C contradict earlier reports (23,38). The earlier studies lacked controls of known processive and nonprocessive enzymes and used amorphous cellulose (RAC) as the substrate in the processivity assays.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The crystal structure of Cel5B supports this suggestion, since the predicted open active site is consistent with a nonprocessive mode of action. Our results indicating the lack of processivity of Cel5B and Cel9C contradict earlier reports (23,38). The earlier studies lacked controls of known processive and nonprocessive enzymes and used amorphous cellulose (RAC) as the substrate in the processivity assays.…”
Section: Discussioncontrasting
confidence: 57%
“…Cel5B and Cel9C are predicted to have N-terminal signal peptides for export across the cytoplasmic membrane by the secretory (Sec) system, but they lack the conserved CTDs that target proteins to the T9SS for secretion across the outer membrane. A previous study indicated that Cel9C was 571 amino acids long and lacked a signal peptide (38), but manual annotation identified a more likely start codon that resulted in a translated protein of 589 amino acids, with an obvious hydrophobic signal peptide at the amino terminus (see Fig. S7 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…The EG‐CMC and XYN‐bw activities of CbGH5 are not cation‐dependent, different from a few Ca 2+ ‐dependent cellulases and xylanases (Yazawa et al ., ; Zhang et al ., ). The enzyme received no negative effect from cations of macronutrients such as Na + , K + , Ca 2+ and Mg 2+ but could be severely inhibited by heavy metal ions, suggesting that CbGH5 could be suitable for usual lignocellulosic treatments but should avoid samples rich in heavy metal such as industrial wastewater.…”
Section: Discussionmentioning
confidence: 97%
“…De acordo com os estudos anteriores realizados ara outras enzimas desta família, a presença de Ca 2+ tem impactado grandemente a estabilidade térmica e afinidade pelo ligante destas enzimas. 189,190 Para investigar a estabilidade estrutural de BlCel9 em diferentes pHs, estudos de estabilidade térmica foi conduzida usando a técnica Thermoflour. Para pHs próximo ao neutro entre 6,6 e 7,0, o Tm máximo foi de 77…”
Section: Parâmetros De Coleta De Dadosunclassified
“…45,53,197 Entretanto, quando avaliada a influência de cálcio na atividade enzimática de BlCel9, não foi observado qualquer aumento; isso sugere que esse íon tem um papel mais estrutural do que funcional, como observado em outros trabalhos em que o cálcio tem importante melhora na termoesbilidade enzimática e aumento da afinidade do substrato dentro do sítio catalítico. 189,190,200 5.1.3.1 Domínio de ligação à celulose Domínios de ligação à celulose da família 3 são largamente observados estando associados à GHs bacterianas. 201 O domínio de ligação à celulose da subfamília 3c, CBM3c, é composto por 9 folhas-beta antiparalelas formadas por 151 resíduos de aminoácidos, apresentando topologia do tipo beta-sandwich e um motivo tipo jelly roll, motivo este observado em estruturas de CBMs da família 3 de homólogos determinadas anteriormente.…”
Section: Estudos Estruturais Por Cristalografia De Raios Xunclassified